"Hieroglyphs of Protest": Internet Memes and the Protest Movement in Russia. Issue 3 (4th May 2022) - Shomova, Svetlana
ABSTRACT: Political Internet memes are an underresearched phenomenon situated at the intersection of digital and political communication. Regarded as a unit of cultural information transmitted online, such a meme can be considered as both a manifestation of anonymous networked creativity and a mechanism of political participation. The article presents the results of an investigation into Internet memes generated by protest discourses on Runet (Russian Internet). The examination of Internet content allows us to draw conclusions as to the thematic emphases of protest actions represented in Runet's memosphere and the specifics of the image of Russian protest as reflected in memes.